2020
DOI: 10.3390/sports8080104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supplementary Strength–Power Training on Neuromuscular Performance in Young Female Athletes

Abstract: This study examined the effects of a short-duration supplementary strength–power training program on neuromuscular performance and sport-specific skills in adolescent athletes. Twenty-three female “Gymnastics for All” athletes, aged 13 ± 2 years, were divided into a training group (TG, n = 12) and a control group (CG, n = 11). Both groups underwent a test battery before and after 10 weeks of intervention. TG completed, in addition to gymnastics training, a supplementary 7–9 min program that included two rounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…In addition, the biological maturation (Tanner stages) of the gymnasts was not examined, which could affect the results of the asymmetries, since it is known that the observed age of the participants is crucial for biological maturation. In the studies with observed isometric knee strength or CMJ parameters, the sample size varied but is comparable to our study Pentidis et al, 2019Pentidis et al, , 2020Thompson et al, 2017), while other studies had larger sample sizes (Bencke et al, 2002;Ceroni et al, 2012;Hall et al, 2016;Karagianni et al, 2020;Kinser et al, 2008;Markström et al, 2019). However, the results showed good reliability for all observed parameters.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In addition, the biological maturation (Tanner stages) of the gymnasts was not examined, which could affect the results of the asymmetries, since it is known that the observed age of the participants is crucial for biological maturation. In the studies with observed isometric knee strength or CMJ parameters, the sample size varied but is comparable to our study Pentidis et al, 2019Pentidis et al, , 2020Thompson et al, 2017), while other studies had larger sample sizes (Bencke et al, 2002;Ceroni et al, 2012;Hall et al, 2016;Karagianni et al, 2020;Kinser et al, 2008;Markström et al, 2019). However, the results showed good reliability for all observed parameters.…”
Section: Discussionsupporting
confidence: 81%
“…The study by Bencke et al (2002) compared CMJ height between gymnasts, swimmers, handball and tennis players and a study by compared CMJ height between gymnasts and a control group after the intervention. They found no significant differences in jump height between the observed groups, unlike the studies by Pentidis et al, (2019Pentidis et al, ( , 2020 that observed gymnasts and a control group of non-athletes, and the studies (Dallas, Kirialanis & Mellos, 2014;Dallas et al, 2019;Hall et al, 2016;Karagianni et al, 2020;Kinser et al, 2008) conducted on a gymnast and a control group after the intervention. The studies reported significant differences in jump height between the observed groups.…”
Section: Discussionmentioning
confidence: 83%
“…Previous data in young female gymnasts indicate that sprint speed plateaus between the late prepubertal and pubertal years, whereas Peak momentum continues to increase (11). Existing training literature has shown equivocal findings, with 8 wk of supplementary plyometric training proving effective at improving young gymnasts’ sprinting abilities (18), but 10 wk of strength and power training failing to significantly improve 10-m sprint performance in young female gymnasts (44). In light of our findings, it appears that NMT can enhance sprint speed in prepubertal gymnasts, although longer periods of training and greater specificity of the exercises selected (i.e., sprinting) may be necessary to realize such improvements.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding strength, it is important for gymnast's performance as has been described in previous studies (French et al, 2004;Mkaouer, Hammoudi-Nassib, Amara & Chaabène, 2018;Sawkzyn et al, 2016). However, gymnasts perform exercises repeatedly, in routines that require a great level of not only strength, but also power, and endurance from the body extremities (Kerr, Hayden, Barr, Klossner & Dompier, 2015). Therefore, a complete proceeding of performance evaluation is more applicable to determine sports performance in gymnastics.…”
Section: Discussionmentioning
confidence: 99%